2017
DOI: 10.1590/1809-4430-eng.agric.v37n1p46-53/2017
|View full text |Cite
|
Sign up to set email alerts
|

Kale Seedlings Production in Different Substrates, Cell Volumes and Protected Environments

Abstract: ABSTRACT:The kale is a brassica, this vegetable presents importance on nutritional and economic patterns. The present study aimed to evaluate the effect of different substrates, trays and protected environment in the formation of kale seedlings. The experiment was conducted in two greenhouses located at the State University of Mato Grosso do Sul -MS. The first environment consisted of an agricultural greenhouse with polyethylene film cover, while the second was an agricultural nursery with monofilament screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Besides reducing sunlight direct incidence on plants by shading with a cover, the protected environment can favor microclimate conditions, protect against pests, and decrease evapotranspiration, strengthening seedlings. Studies have demonstrated that plant species interact differently when under certain shading levels, which can provide seedlings of different sizes (Costa et al, 2017;Cruz et al, 2016;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides reducing sunlight direct incidence on plants by shading with a cover, the protected environment can favor microclimate conditions, protect against pests, and decrease evapotranspiration, strengthening seedlings. Studies have demonstrated that plant species interact differently when under certain shading levels, which can provide seedlings of different sizes (Costa et al, 2017;Cruz et al, 2016;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%